PAIN AND HEALTH-RELATED QUALITY OF LIFE AMONG OLDER PEOPLE WITH DIABETIC FOOT ULCER: A LITERATURE REVIEW (Proceedings of the Global Public Health Conference, 2018)
Little is known about how pain contributes to diabetic foot ulcer related health-related quality of life. The aim of this review was to explore the relationships between diabetic foot ulcer pain and health-related quality of life among older people. A literature review was conducted. MEDLINE (Ovid), the Cumulative Index of Nursing and the Allied Health Literature (CINAHL), and British Nursing Index (BNI) was carried out using MeSH terms diabetic foot ulcer, foot ulcer, pain, quality of life, health-related quality of life, and all studies published between 2000 and 2016 were considered in with both qualitative and quantitative approaches and in Malay and English. Thus, no restrictions were applied as regards study design. Twenty-seven studies were included; twenty- three used quantitative methods and four employed qualitative methods. No study focused only on older people. Pain was the factor most frequently identified as affecting health-related quality of life. It is, however, hard to draw any firm conclusions about older people's pain and health-related quality of life because of the lack of studies including older people. Thus, research about diabetic foot ulcer pain and health-related quality of life, especially focusing on the older people with diabetic foot ulcer, is needed.
Keywords: diabetic foot ulcer; pain; health-related quality of life; older people